Antibacterial effect of a gingival patch containing nano-emulsion of red dragon fruit peel extract on Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum assessed in vitro - Indeswati Diyatri; Wisnu Setyari Juliastuti; Rini Devijanti Ridwan; Ghinalya Chalbi Ananda; Fuad Adhi Waskita; Nita Vania Juliana; Shafa Putri Khansa; Reinaya Tifa Pratiwi; Cindy Ramadhan Putri (Elsevier, 2023)
Background: The most common bacteria causing periodontitis were Porphyromonas gingivalis, Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans. At present, plants are considered a valuable source of natural materials for use in the development of antimicrobial, anti-inflammatory and antioxidant agents. Hylocereus plyrhizus or red dragon fruit peel extract (RDFPE) contains terpenoids, and flavonoids can be an alternative. The gingival patch (GP) has been designed to ensure drug delivery and absorption into tissue targets. Objective: To assess the effect of a mucoadhesive gingival patch containing nano-emulsion of red dragon fruit peel extract (GP-nRDFPE) in inhibiting Porphyromonas gingivalis, Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans as compared to control groups. Material and method: Inhibition by diffusion method was carried out in Porphyromonas gingivalis, Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans medium. The test material was gingival patch mucoadhesive containing nano-emulsion red dragon fruit peel extract (GP-nRDFPR), gingival patch mucoadhesive containing red dragon fruit peel extract (GP-RDFPE), gingival patch mucoadhesive containing doxycycline (GP-dcx) and blank gingival patch (GP), conducted in four replications. The differences in the inhibition were analyzed using ANOVA and post hoc tests (p < 0.05). Result: GP-nRDFPE showed higher inhibition in Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum compared to GP-RDFPE at the concentrations 3.125% and 6.25% (p < 0.05). Conclusion: The GP-nRDFPE showed better anti-periodontic bacteria to Porphyromonas gingivalis, Fusobacterium nucleatum, and Aggregatibacter actinomycetemcomitans in line with its concentration. This is assumed that the GP-nRDFPE can use as periodontitis treatment.